Cognitive Tools in Medical Teamwork: The Spatial Arrangement of Patient Records - Bång, M.; Timpka, T. (Methods of Information in Medicine, 2003)
Objectives: As a preliminary for the design of Computer-Based Patient Records, the aim of this paper is to build an understanding of the roles physical artifacts like paper-based patient records play in supporting cognition and collaboration in the health-care settings.Method: A small ethnographically-informed study was conducted in the emergency room at a 250-bed hospital in Sweden from the perspective of Distributed Cognition.Results: To track work-in-progress, clinicians placed patient records on a desk to form a shared public display that represented the current problem state for the health-care team. The results of the study suggest that the patient records and other physical artifacts are used by clinicians in different ways to form cognitive tools that offload memory tasks and support joint attention and collaboration.Conclusion: To design Computer-Based Patient Records that more appropriately support cognition and teamwork, it is important to investigate how clinicians make use of the paper-based patient records. Practitioners take advantage of existing tools frequently to deal with cognitively demanding tasks and collaboration issues.
Keywords: Cognitive artifacts; distributed cognition; information systems design; computer-based patient records; cooperative work